TRANSFORMATION OF INFORMATION NEEDS FOR FINANCES IN THE INFORMATION ECONOMY - Боярко, Ірина; Голуб, Роксолана (Socio-economic relations in the digital society, 2019)
The article defines the directions of the transformation of information needs of fi nance in the process ofcomplex socio-economic transformations that accompany the formation and development of an information society. The starting point of the research is that the growth of the role of quality of the formation, functioning and satisfaction of information needs is the main tool of management and development in the conditions of information economy. The strategic orientation of information needs is based on the strengthening of the objective connection between operational, current and strategic information, systematic and comprehensive study of the impact of internal and external environmental factors on the current and prospective state of objects of social activity, including finance It was established that the economy of information society is characterized by gradual leveling of diff erences between information needs and information in fi nancial relations in view of acceleration of information and communication processes. Transparency of information systems, which involves both the openness of information and the openness ofinformation needs of financial relations subjects, promotes the gradual expansion of information on financial relations and, accordingly, the erosion of the content between the mand information on finances. The directions of transformation of information needs are justifi ed from the point of view of modern concepts ofinformation ontology — activity, systemic, cognitive and temporal. Structural-logical model of transformation of information needs of fi nance in the conditions of information economyis developed. The definition of information needs of finance is presented, which refl ects the specifi cs that are determined by the directions of their transformation. It is proved that the information needs of fi nance correspond to the profi le of fi nancial activity and the peculiarities of information and communication interaction in the information society.
Keywords: finance; information economy; information needs